Geographies of Difference: Transborder Organizing and Indigenous Women's Activism - Blackwell, Maylei (Social justice, 2015)
The article discusses the struggle of women activists in Oaxaca, Mexico and California, who share transborder goals, in navigating local realities while participating in cross-border campaigns. Topics discussed include gender discrimination faced by indigenous Mexican women organizers, transnational organizing in the Mexican and American society, and the experiences of activists with the indigenous social movement Frente Indígena de Organizaciones Binacionales (FIOB).